The Age Dependent Activities of Digestive Enzymes in Rasbora, Rasbora lateristriata Blkr., (Pisces: Cyprinidae) - Untung Susilo; Purnama Sukardi; Ridwan Affandi (Universitas Jenderal Soedirman, 2018)
This study was to evaluate the digestive enzyme activity included a total protease, trypsin, chymotrypsin, lipase, amylase, cellulase and alkaline phosphatase in Rasbora. This research was carried out using three different ages (2, 4 and 6 months) and in each age consisted of six groups (replicates). In this study 150 fish (±2 months age), 120 fish (± 4 months age) and 90 fish (± 6 months age) were used. All digestion enzyme activity was measured by the spectrophotometric method, except the lipase activity was by the titration method. The results showed that the distinctness of age resulted in a significant difference on total protease, trypsin, lipase, cellulase and alkaline phosphatase (P <0.05), but no significant difference in amylase activity (P> 0.05). Total protease and trypsin activities were higher in fish of age two months than fish age four and six months, but the activity of lipase, cellulase and alkaline phosphatase were higher in fish age of four months compared to two months age fish. Fish, with distinct age has the different nutrient digestion capacity as expressed by differences in the activity of the enzyme digestion, except amylase. These results contribute to the future development of digestive physiology, especially in Rasbora.Key Words: alkaline phosphatase, carbohydrase, lipase, protease, Rasbora